1999
DOI: 10.1046/j.1440-1622.1999.01702.x
|View full text |Cite
|
Sign up to set email alerts
|

The Blood Supply of the Biliary Ductal System and Its Relevance to Vasculobiliary Injuries Following Cholecystectomy

Abstract: A knowledge of the blood supply of the normal biliary system and the collateral hilar plate arterial plexus forms the anatomical foundation for successful reconstructive surgery, not only in vasculobiliary injuries following cholecystectomy, but also for a wide range of hepatobiliary procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
67
0
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 6 publications
1
67
0
4
Order By: Relevance
“…10 The supraduodenal CBD including CHD is primarily supplied by 6-8 small arteries of about 0.30 mm in diameter having a longitudinal ascending or descending course and anastomosing with each other. The most prominent axial vessels run along the lateral borders and named as 3 o'clock and 9 o'clock arteries, 7,11 right and left arch arteries, 12 right and left marginal arteries 8 [ Figure 2]. Ascending branches arise from the posterior superior pancreaticoduodenal artery (PSPDA -frequently mentioned as retroduodenal artery in earlier literature), supraduodenal artery, gastroduodenal artery (GDA) and retroportal artery, while descending branches come from right hepatic artery (RHA), cystic artery.…”
Section: Arterial Supply Of Biliary Tractmentioning
confidence: 99%
See 2 more Smart Citations
“…10 The supraduodenal CBD including CHD is primarily supplied by 6-8 small arteries of about 0.30 mm in diameter having a longitudinal ascending or descending course and anastomosing with each other. The most prominent axial vessels run along the lateral borders and named as 3 o'clock and 9 o'clock arteries, 7,11 right and left arch arteries, 12 right and left marginal arteries 8 [ Figure 2]. Ascending branches arise from the posterior superior pancreaticoduodenal artery (PSPDA -frequently mentioned as retroduodenal artery in earlier literature), supraduodenal artery, gastroduodenal artery (GDA) and retroportal artery, while descending branches come from right hepatic artery (RHA), cystic artery.…”
Section: Arterial Supply Of Biliary Tractmentioning
confidence: 99%
“…A marginal artery on the posterior surface of CBD, probably similar to the retroportal artery, was also reported in few cases. 11 Rath et al 12 described three patterns of arterial vascularization named as axial pattern with right and left arches, ladder pattern with horizontally directed branches and mixed pattern [ Figure 3]. The left marginal artery (3 o'clock artery) is present in 95% cases 8 and arises inferiorly from PSPDA or GDA and joins the RHA superiorly.…”
Section: Arterial Supply Of Biliary Tractmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the arterial supply of hilar bile duct is a collateral system, where the right and left hepatic arteries communicate freely via the hilar plate arterial plexus. 12 Hence, ischemia seldom happens. The proximal bile duct stump should be dissected at the level of hepatic duct convergence, especially in the case of injury of the right hepatic artery.…”
Section: Discussionmentioning
confidence: 99%
“…However, these arteries do not continue cranially into the right and left HDs. Vellar (4) showed that the 9 o'clock artery joins the right hepatic artery or one of its branches proximal to the right HD in most cases, whereas the 3 o'clock and the transverse hilar arteries terminate in the peribiliary plexus of the left/both HDs. Besides, the orientation and number of HDs in the graft are variable in more than half the cases, making 3 and 9 o'clock positions irrelevant.…”
mentioning
confidence: 99%